INFLUENCE OF IODINE DEFECTS ON THE FEATURE OF CLINICS OF NEUROLOGICAL SIGNS IN PATIENTS WITH DISCIRCULATORY ENCEPHALOPATHY (Archive of Conferences, 2021)
The basis of chronic vascular insufficiency of cerebral circulation are diverse, diffuse lesion cerebral brain manifested by neurological and neuropsychological disorders ( 1, 3 ). According to statistics , independent research in Z over 20 accrued to date million . a person with discirculatory encephalopathy, and most importantly , there is an increase in this pathology. The importance of solving the problem is due not only to the high prevalence, but also the significance of the problem , as a factor precursor to the development of a brain catastrophe , and as a consequence , social disability . That is, the prevention of a decrease in discirculatory encephalopathy and the provision of competent assistance to patients with cerebrovascular pathology is a paramount task. The reason for the disruption of the cerebral structure of their chronization depends on many factors, this is arterial hypertension, atherosclerosis, diabetes mellitus, etc., but one should not fail to assess the role of endocrine pathology in the formation of discirculatory encephalopathy ( 2, 5 ). Specific gravity hypothyroidism among pathologies of endocrine system is growing every year, especially troubled area in Uzbekistan where the incidence is 15% of the population (data Saidrasulovoy MA, 2019 g of . ). Among pregnant women living in conditions of severe iodine deficiency of the Republic of Uzbekistan, thyroid pathology is found in 91.1% of cases, including autoimmune thier e oidit Hashimoto in 24% ( 6, 8 ). In the older generation, as a rule , primary hypothyroidism occurs due to a lack of iodine in the body, protein and selenium, as well as due to the intake of drugs with anti - thyroid action (antipsychotics, tranquilizers) ( 4, 7 ). Diagnosis is difficult at this age, as masquerades as many diseases - coronary heart disease , arterial th hy e rtenziya, depression . Neurological disorders in the background of hypothyroidism have a special significance, and in recent years, promoted to leading positions, and diagnosis and treatment of patients with dyscirculatory encephalopathy hypothyroidism , with tal and the most urgent issues of neurology.